Combining ability estimates and heterosis analysis on major yield attributing traits and lint quality in American cotton (Gossypium hirsutum L.) - S. Mudhalvan1 *, S. Rajeswari2 , L. Mahalingam2 , P. Jeyakumar3 , M. Muthuswami4 and N. Premalatha2 (Electronic Journal of Plant Breeding, 2021)
Six cotton lines and five testers were crossed in a line x tester mating design in 2019. Thereby hybrids along with 11 parents and a standard check were evaluated for combining ability and standard heterosis. Observations on sympodial branches per plant, the number of bolls per plant, boll weight, Ginning Out Turn, staple length and seed cotton yield per plant were recorded. Among the parents, GJHV 534, TVH 002, NDLH 32, TCH 1894 and RAHC 1040 displayed higher positive gca effects for the number of bolls/plant, sympodial branches/plant, span length, seed cotton yield and ginning outturn percentage. Such results suggested that all these five parents were good general combiners covering the yield contributing traits studied and may be preferred for hybridization and selection programmes. The crosses viz., TVH 002 x RAHC 1040, GJHV 534 x RAHC 1040 and TCH 1894 x NDLH 32 with higher estimates of sca effects for almost all the traits and also were observed with higher heterotic effects. Thus these hybrids could be potential hybrids for the exploitation of heterosis in cotton.